(3GdJMhd ef GdbWGY GdYGe Gdi GdbWGY GdNGU (B/s - (3Gdbgjhj, djK YHO Gddgs; (3GdhGOj, HdGd eMehOs ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2012)
(3JWhQGJ OhQ GdOhdI aj Xd GdJMhdGJ GdGbJUGOjI h GdJMhd ef GdbWGY GdYGe Gdi GdbWGY GdNGU (B( (3YedjI GdNUNUI (B)(3h GdJQJjHGJ GdeDSSjI ddNUNUI h CSGdjHgG , GdeQGMd h GdGLQGAGJ GdeUGMHI dYedjI GdJMhd h GdeTGcd GdJj JYJQV YedjI GdJMhd eY GdJWQb Gdi hGbY GdJLQHjI GdGQOfjI aj NUNUI bWGY GdGJUGdGJs
Keywords: (3GdJZjQ GdELJeGYjs; (3GdbWGY GdNGUs; (3GdbWGY GdYGes